Nosocomial acquisition of influenza is associated with significant morbidity and mortality: Results of a prospective observational study. Issue 10 (October 2022) - Snell, L.B.; Vink, J.P.; Verlander, N.Q.; Miah, S.; Lackenby, A.; Williams, D.; Mitchell, H.; Beviz, C.; Kabia, M.; Cunningham, E.; Batra, R.; Edgeworth, J.D.; et al.
Abstract: Background: Nosocomial acquisition of influenza is known to occur but the risk after exposure to a known case and the outcomes after acquisition are poorly defined. Methods: Prospective observational study of patients exposed to influenza from another patient in a multi-site healthcare organisation, with follow-up of 7 days or until discharge, and PCR-confirmation of symptomatic disease. Multivariable analysis was used to investigate association of influenza acquisition with high dependency unit/intensive care unit (HDU/ITU) admission and in-hospital mortality. Results: 23/298 (7.7%) contacts of 11 cases were subsequently symptomatic and tested influenza-positive during follow-up. HDU/ITU admission was significantly higher in these secondary cases (6/23, 26%) compared to flu-negative contacts (20/275, 7.2%; p = 0.002). In-hospital mortality was significantly higher in secondary cases (5/23, 21.7%) compared to flu-negative contacts (11/275, 4%; p < 0.001). In multivariable analysis, age (OR 1.25 95% CI: 1.01–1.54, p = 0.02) and being a secondary case (OR 4.77, 95% CI: 1.63–13.9, p = 0.008) were significantly associated with HDU/ITU admission in contacts. Age (OR 1.00, 95% CI: 0.93–1.00, p = 0.02),  being a secondary case after exposure to influenza (OR 3.81, 95% CI 1.09–13.3, p = 0.049) and co-morbidity (OR 1.29 per unit increment in the Charlson score, 95% CI 1.02–1.61, p = 0.03) were significantly associated with in-hospital mortality in contacts. Conclusions: Nosocomial acquisition of influenza was significantly associated with increased risk of HDU/ITU admission and in-hospital mortality.